Pengaruh Pelatihan Bersertifikat, Karakteristik Lulusan, dan Disabilitas Terhadap Pengangguran Usia Muda di Indonesia - Ariful Romadhon; Adilla Zikra (Seminar Nasional Official Statistics, 2022)
Youth unemployment is one of the important issues in today's employment. In August 2021, the open unemployment rate (TPT) of young age group was 19.55 percent. In other words, one in five youth labor force was unemployed. In fact, this figure is five times higher than the adult age group. The young age group is expected to be productive so as not to become a development burden because Indonesia has entered the era of the demographic dividend, which is the time when the dependency rate is lowest due to the large increase in the productive age group which is expected to take place in 2012-2037. Using binary logistic regression analysis, this study aims to analyze the effect of certified training, graduate characteristics, and disabilities on youth unemployment in Indonesia. The results showed that partially, using the socio-demographic control variable, the youth labor force who had attended certified training in the past had a lower tendency to be unemployed. On the other hand, those who are classified as fresh graduates and have disabilities have a higher tendency to be unemployed. Certified training plays an important role in increasing knowledge and skills so that they are more ready to work. For those who are fresh graduates who still lack work experience, the employment link and match program can be a bridge to be able to enter the Business and Industrial World (DUDI) according to the majors taken. Furthermore, special programs are needed for people with disabilities to facilitate their access and increase their opportunities to be able to play an active role in the labor market. Keywords: Youth unemployment, certified training, graduate characteristics, disability, link and match employment.